Study and applications of a pneumatic acceletator for variety speed of punching - Mohammad Firdaus, Shamsudin (2008)
Pneumatic accelerator is a device to produce energy by using air as source. It can be incorporated into mechanical press to release the variety speed of punching process. The accelerator can be adapted easily onto conventional presses has been used and analysis the thick sheet metals in this study. Most of the conventional presses have a fix speed and no specific speed for a different thickness and types of material. As known, they are needed to use different speed and pressures are given to produce high surface quality and they do not need finishing process. After metal forming operation, analysis by comparing between observation and finite element analysis (FEA) by using ALGOR to verify when increasing the speed and pressure are necessary to produce high surface quality. Expectations from this work are reduced distortion rates, increased surface quality and precise dimensions in metal forming operations. From the performance test, the accelerator is able to achieve variety speed and energy which require for punching process of different thickness of thick sheet metals.